PEMBIAYAAN SYARIAH SEKTOR PERTANIAN - Faoeza Hafiz Saragih (JURNAL AGRICA, 2017)
Indonesia is an agriculture country, which means the agricultural sector was an important role in the Indonesian economy. One of the main problems faced by the agricultural sector is the lack of farmer capital in developing his farm, the farmer is not able to fund their farm with their own funds. The agricultural sector is known to be quite risky and uncertain and this make the financial institutions to fund this sector is relatively low. Other financing alternatives that may be the solution for farmers is the shariah financing institutions. Some shariah products which can be applied to agribusiness, among others: Mudharabah, Musharaka, muzara'ah, musaqoh, bai 'murabahah, bai istishna, bai' as-salam and rahn.Keyword: Agriculture, Financing, Shariah